Partial Gene Deletions of PMP22 Causing Hereditary Neuropathy with Liability to Pressure Palsies. (20th November 2014) - Cho, Sun-Mi; Hong, Bo Young; Kim, Yoonjung; Lee, Sang Guk; Yang, Jin-Young; Kim, Juwon; Lee, Kyung-A
Abstract : Hereditary neuropathy with liability to pressure palsies (HNPP) is an autosomal neuropathy that is commonly caused by a reciprocal 1.5 Mb deletion on chromosome 17p11.2, at the site of the peripheral myelin protein 22 ( PMP22 ) gene. Other patients with similar phenotypes have been shown to harbor point mutations or small deletions, although there is some clinical variation across these patients. In this report, we describe a case of HNPP with copy number changes in exon or promoter regions of PMP22 . Multiplex ligation-dependent probe analysis revealed an exon 1b deletion in the patient, who had been diagnosed with HNPP in the first decade of life using molecular analysis.